2011
DOI: 10.1371/journal.pone.0016892
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Efflux Pumps in Chloramphenicol Selected Strains of Burkholderia thailandensis: Proteomic and Mechanistic Evidence

Abstract: Burkholderia is a bacterial genus comprising several pathogenic species, including two species highly pathogenic for humans, B. pseudomallei and B. mallei. B. thailandensis is a weakly pathogenic species closely related to both B. pseudomallei and B. mallei. It is used as a study model. These bacteria are able to exhibit multiple resistance mechanisms towards various families of antibiotics. By sequentially plating B. thailandensis wild type strains on chloramphenicol we obtained several resistant variants. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Consistent with its nature as a dipeptide amide with two positive charges at physiological pH, PA␤N has been noted since its discovery for its membrane-permeabilizing effect (particularly in the absence of a functional MexAB-OprM pump) at a level of 16 g/ml, especially in Mg 2ϩ -poor media (60,1005). In combinational studies with antibiotics, PA␤N has often been used at concentrations of Ͼ20 g/ml (Table 5) (60,550,1005). Several more recent studies have also highlighted such OM-permeabilizing effects (974,975,1006,1007), although their conclusions need to be examined carefully, as discussed above (see Efflux Pump Inhibitors).…”
Section: Methodological Considerationsmentioning
confidence: 87%
See 2 more Smart Citations
“…Consistent with its nature as a dipeptide amide with two positive charges at physiological pH, PA␤N has been noted since its discovery for its membrane-permeabilizing effect (particularly in the absence of a functional MexAB-OprM pump) at a level of 16 g/ml, especially in Mg 2ϩ -poor media (60,1005). In combinational studies with antibiotics, PA␤N has often been used at concentrations of Ͼ20 g/ml (Table 5) (60,550,1005). Several more recent studies have also highlighted such OM-permeabilizing effects (974,975,1006,1007), although their conclusions need to be examined carefully, as discussed above (see Efflux Pump Inhibitors).…”
Section: Methodological Considerationsmentioning
confidence: 87%
“…Thus, studies with carelessly chosen concentrations may inappropriately estimate the role of efflux mechanisms in clinical isolates. Consistent with its nature as a dipeptide amide with two positive charges at physiological pH, PA␤N has been noted since its discovery for its membrane-permeabilizing effect (particularly in the absence of a functional MexAB-OprM pump) at a level of 16 g/ml, especially in Mg 2ϩ -poor media (60,1005). In combinational studies with antibiotics, PA␤N has often been used at concentrations of Ͼ20 g/ml (Table 5) (60,550,1005).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of this operon is governed by the LysR-type regulator BpeT, which is encoded by a gene located immediately upstream of the llpEbpeEF-oprC operon. BpeEF-OprC has been shown to efflux trimethoprim when expressed in Pseudomonas aeruginosa (18), in Burkholderia thailandensis isolates that are resistant to chloramphenicol (19), and in B. pseudomallei isolates that express BpeEFOprC as a result of a BpeT truncation (21). To investigate a potential contribution of this efflux pump to trimethoprim resistance in clinical and environmental B. pseudomallei isolates, a 4,314-bp segment of the llpE-bpeEF-oprC operon was deleted from 11 trimethoprim-resistant isolates and trimethoprim-susceptible reference strains 1026b and E0237.…”
Section: Resultsmentioning
confidence: 99%
“…B. pseudomallei co-trimoxazole resistance was previously documented in regions where the disease is endemic (12)(13)(14)(15)(16), and rates range from 2.5% in Australia (13) to 13 to 16% in Thailand (12,14). Previous studies have identified and characterized trimethoprim resistance mechanisms including resistant dihydrofolate reductases in other organisms, such as Escherichia coli (11,17), but in B. pseudomallei, trimethoprim resistance has been studied only indirectly in surrogate (18) or closely related (19) bacteria, showing that efflux could play an important role in resistance. The objective of this study was to identify and characterize the mechanism responsible for trimethoprim resistance in clinical and environmental B. pseudomallei isolates from northeast Thailand and northern Australia.…”
mentioning
confidence: 99%